PERANAN PRAKTEK TOTAL QUALITY MANAGEMENT DAN KEPEMIMPINAN DALAM MEMENGARUHI KEPUASAN DAN LOYALITAS KARYAWAN : STUDY PADA CLARION HOTEL MAKASSAR. - Wahyudi Wahyudi (University of Merdeka Malang, 2016)
Abstract :The aims of this study was to investigate the influence effect of direct TQM practices and leaderships on employees satisfactions and loyalties on Clarion Hotel Makassar. In addition, it was done to investigate indirect effect of TQM practices and leaderships on employees loyalties through employees satisfactions. In this study, the data were collected using a questionnaire with Likert scale, and then distributed to 157 employees of Clarion Hotel. Partial Least Square (PLS) was used to analyze the data. The finding of this study reveals that TQM practices and Leaderships have a positive and significant effect on employees satisfactions and loyalties. Furthermore, in this study was found that TQM practices and Leaderships have a positive and significant effect on employees loyalties through employees satisfactions, so employees satisfaction could mediate the effect of TQM practices and leaderships on employee loyalty.